Analisis Konsep Religiusitas Islam pada Keputusan Nasabah Menggunakan ATM dan Mobile Banking di PT. Bank Sumut Syariah - Inda Novita Sari; Kamaliah R; Khairunnisa Khairunnisa (AGHNIYA : Jurnal Ekonomi Islam, 2022)
This research aims to find out the decisions of customers using ATMs and mobile banking in the concept of Islamic religiosity at PT. Bank Sumut Syariah. This type of research is qualitative research, with research subjects, namely customers and banks as the main information. Religiosity refers more to the quality aspects of religious people. Religion and religiosity support each other and complement each other because they are both logical consequences of human life that has two poles, namely the pole of personal life and the pole of togetherness in society. Customers and banks both benefit from mobile banking and ATM services. Customers will get banking information quickly, effectively and efficiently, and can reduce customer waiting times in conducting banking transactions. While for the bank itself, products with information technology make it easier for them to reduce the work of employees, especially tellers and or customer service.